Clonal relatedness of coagulase-positive staphylococci among healthy dogs and dog-owners in Spain. Detection of multidrug-resistant-MSSA-CC398 and novel linezolid-resistant-MRSA-CC5 - Abdullahi, Idris Nasir; Lozano, Carmen; Zarazaga, Myriam; Saidenberg, Andre Becker Simoes; Stegger, Marc; Torres, Carmen (Frontiers in Microbiology, 2023)
Nasal carriage of coagulase-positive staphylococci (CoPS) in healthy dogs could indicate increased risks of colonization for in-contact people or vice versa. This study determined the nasal carriage rate of CoPS among healthy dogs and in-contact people, their genotypic characteristics and phylogenetic relatedness. Nasal samples were collected from 27 households (34 dogs and 41 humans) in Spain. Staphylococci were identified by MALDI-TOF-MS, their antimicrobial resistance (AMR) genes and spa-types were tested by PCR/sequencing. The relatedness of CoPS from the same households was assessed by core genome single nucleotide polymorphisms (SNPs) analyses. Staphylococcus aureus carriage was found in 34.1% of humans (including one methicillin-resistant S. aureus MRSA-CC5-t2220-SCCmec type-IV2B) and 5.9% of dogs; Staphylococcus pseudintermedius in 2.4% of humans and 32.4% of dogs; while Staphylococcus coagulans was only detected in dogs (5.4%). Remarkably, one human co-carried S. aureus/S. pseudintermedius, while a dog co-carried the three CoPS species. Household density was significantly associated with S. pseudintermedius carriage in households with > than 1 dog and > than 1 human (OR=18.10, 95% CI: 1.24-260.93, p=0.034). Closely related (<15 SNPs) S. aureus or S. pseudintermedius were found in humans or dogs in three households. About 56.3% S. aureus carriers (dog or human) harboured diverse within-host spa-types or AMR genotypes. Ten clonal complexes (CCs) were detected among the S. aureus, of which methicillin-susceptible S. aureus-CC398-IEC-type C (t1451 and t571) was the most frequent, but exclusive to humans. S. aureus and S. pseudintermedius isolates harboured resistance genes or mutations associated to 9 classes of antimicrobials including linezolid (G2261A & T1584A point mutations in 23S rDNA). The S. coagulans isolates were susceptible to all antimicrobials. Most of the S. pseudintermedius carried lukS/F-I, siet, and sient genes, and all S. aureus were negative for lukS/F-PV, tst-1, eta and etb genes. Clonally related human-to-human MSSA and dog-to-human MSSP were found. The detection of the MSSA-CC398 clade highlights the need for its continuous surveillance from One Health perspective.